The adoption of artificial intelligence in programmatic advertising in South Africa based on relative ease and usefulness using the diffusion of technology theory - Myburgh, Suzanne (University of Pretoria, 2025)
Mini Dissertation (MBA)--University of Pretoria, 2024.